DESCENT OF MOLLUSKS PRODUCTION TOWARD SOCIAL ECONOMICS LIVELIHOOD’S TRADITIONAL FISHERMEN IN BAGAN ASAHAN PEEKAN VILLAGE TANJUNG BALAI SUBDISTRICT ASAHAN REGENCY SOUTH SUMATERA PROVINCE - Sihotang, Meriaty; Hamid, Hamdi; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
This Research had done on April 2017 in Bagan Asahan Pekan village Tanjung Balai Subdistrict Asahan Regency South Sumatera Province. The method of this research is survey method. This research aims to observed change of social economics livelihood’s fishermen after descent of mollusks production in Bagan Asahan Pekan Village. Collecting data had done with observation technique, quisioner and interview technique and anlysis data is descriptif analysis and test t-paired.The result of this research point out that descent of mollusks production have influential to change of social such as change of means of livelihood, education and relation or interaction with family and the other. While change of economics such as more descent income and expulsion’s fishermen.Keyword: Production, Mollusks, Livelihood, Social Economics